2017
DOI: 10.1038/nphoton.2017.35
|View full text |Cite|
|
Sign up to set email alerts
|

Single-photon imager based on a superconducting nanowire delay line

Abstract: Detecting spatial and temporal information of individual photons by using singlephoton-detector (SPD) arrays is critical to applications in spectroscopy, communication, biological imaging, astronomical observation, and quantum-information processing. Among the current SPDs 1 , detectors based on superconducting nanowires have outstanding performance 2 , but are limited in their ability to be integrated into large scale arrays due to the engineering difficulty of high-bandwidth cryogenic electronic readout [3][… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(122 citation statements)
references
References 38 publications
2
120
0
Order By: Relevance
“…[6], we have attributed this discrepancy to underestimating the kinetic inductivity increase in the shunted region due to suppression of superconductivity (the calculations assume a single L k value which is estimated for the unshunted region). Furthermore, we have also observed that the relative alignment of the metal and the NbN heavily influenced the biasing conditions 3 . This behavior also suggests large kinetic inductivity difference between the shunted and the unshunted regions and requires placement of the metal layer as close as possible to (but not in contact with) the yTron.…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…[6], we have attributed this discrepancy to underestimating the kinetic inductivity increase in the shunted region due to suppression of superconductivity (the calculations assume a single L k value which is estimated for the unshunted region). Furthermore, we have also observed that the relative alignment of the metal and the NbN heavily influenced the biasing conditions 3 . This behavior also suggests large kinetic inductivity difference between the shunted and the unshunted regions and requires placement of the metal layer as close as possible to (but not in contact with) the yTron.…”
Section: Methodsmentioning
confidence: 77%
“…Detection of single-photons is essential to applications such as optical communications, astronomical measurements, and quantum-information processing. Superconducting nanowire single-photon detectors (SNSPDs) are prominent tools for these applications because of their > 90% detection efficiencies, near GHz count rates, few picosecond timing jitter, broad spectral sensitivity from ultra-violet to infrared wavelengths, and sub-Hz dark count rates [1,2,3].…”
Section: Introductionmentioning
confidence: 99%
“…As recent research results indicate, they can in principle resolve photon numbers, but as of now there is no practicable and commercially available implementation using this capability. The same holds true for achieving 2D spatial resolution or the arrangement as 1D detector array …”
Section: Quantum Imaging Device Developmentmentioning
confidence: 86%
“…Cryogenic-based single-photon detectors demonstrate high quantum efficiency (QE) at visible and near-infrared (NIR) wavelengths [10], low dark count rate, picosecond pulse-to-pulse timing jitter, and a gigahertz counting rate. SnSPDs are also recently being used with "imaging" capabilities [13].…”
Section: Single-photon Detectorsmentioning
confidence: 99%